THE Investigation of Proximate Analysis of Coal and Coconut Shell – A Review - Ramesh, Sharvin; Mat Isa, Norasikin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The power generation in Malaysia has grown so widely and they are dependance towards fossil fuel sources has invited harmful effects to the nature. This research is done to investigate the proximate analysis of coal and CSP via ASTM testing and their efficiency to generate power. In this experiment, coal and coconut shell are grounded into particles by a ball mill and went through ASTM E871, E872 and D1102 for proximate analysis. The findings showed the moisture analysis, volatile matter, ash content, fixed carbon and heating value of both coal and coconut shell. The efficiency evaluated showed that coal can be replaced with coconut shell for power generation as it is less harmful to the nature and has better combustion efficiency.